Peran Psikologi dalam Pendidikan Islam - Hudallah, Hudallah; Rokhimah, Siti (TSAQOFAH, 2026)
Islamic education aims to develop learners’ potential in a holistic manner, encompassing cognitive, emotional, social, and spiritual dimensions in accordance with human fitrah, thereby requiring support from psychology to enable educators to understand learners’ characteristics and needs at each stage of development. This study aimed to describe the role of psychology in Islamic education, the psychological approaches that support learning and the formation of Islamic character, the forms of integrating psychology into curricula and teaching methods, as well as the obstacles and solutions in its implementation within Islamic educational settings. The findings indicate that an understanding of developmental psychology enables educators to align instructional methods and moral upbringing with learners’ psychological readiness. Islamic psychological approaches contribute to creating humanistic learning, enhancing learning motivation, and more effectively internalizing the values of tauhid and akhlakul karimah. The integration of psychology into the curriculum and teaching methods of Islamic education supports the realization of holistic, learner-centered learning oriented toward the formation of an Islamic personality. Nevertheless, the application of psychology in Islamic education continues to face various challenges, including teachers’ limited understanding of psychological concepts, insufficient training, and dichotomous views between religious and general sciences. Accordingly, it is necessary to strengthen teachers’ competencies, develop teacher education curricula that are integrated with Islamic psychology, and foster collaboration between psychologists and Islamic education practitioners. This study affirms that Islamic psychological approaches are a crucial element in realizing Islamic education that is effective, humanistic, and oriented toward the comprehensive character formation of learners.